Epitheliotrophic Effect of Autologous Serum in Persistent Corneal Epithelial Defects - Abdul Bari Khan, Aneeq Ullah Baig Mirza, Naheed Ghani (Pakistan Journal of Ophthalmology, 2008)
Purpose: To evaluate the efficacy and complications of autologous serum in cases of persistent corneal epithelial defect (PED). Material and Methods: Patients with PED unresponsive to conventional lubricant treatment were included in this clinical, prospective study which was conducted at IIMCT and Railways teaching Hospital. Patients were examined on day 1 and appropriate treatment including lubricant therapy was instituted. Subsequently, they were examined after 3 weeks and started on 20% autologous serum eye drops in cases of PED. All the other previously used lubricant therapy was stopped. Then, they were examined every 2 weeks for the next three visits. At each visit, in addition to routine eye examination some additional tests were performed i.e. Slitlamp examination for corneal epithelial defects, marginal tear strip evaluation, Schirmer’s test without anesthesia, tear film breakup time, fluorescein and rose Bengal staining and corneal sensitivity. The healing was defined as effective if occurred within 2 weeks of initiating serum therapy, partially effective if occurred within one month and ineffective if didn’t occur within one month. Results: A total of 17 eyes in 10 patients were studied. The local spectrum of indications was severe vernal limbitis with keratopathy (6 eyes, 35.3%), keratoconjunctivitis sicca (7 eyes, 41.1%), drug toxicity (1 eye, 5.9%), lime instillation (2 eyes, 11.8%) and trophic ulcer (1 eye, 5.9%). Healing in 9 eyes occurred within 2 weeks and in 3 eyes within further 2 weeks. In 5 eyes, healing didn’t occur within one month. All the patients were able to complete the follow-up of the study. Accordingly, healing was declared as effective in 9 out of 17 eyes (52.9%), partially effective in 3 out of 17 eyes (17.7%) and ineffective in 5 out of 17 eyes (29.4%). There were no adverse effects except for one red eye without discharge. Response rate was excellent in all except those with severe keratoconjunctivitis sicca (KCS) and below-normal Schirmer’s test value before serum therapy. The mean duration of PED before initiating serum therapy was compared between the effective and ineffective groups. Independent sample t-test was applied and the difference was found to be highly insignificant (p value 0.537). Conclusion: Autologous serum was considered effective in majority of the cases with PED recalcitrant to conventional lubricant therapy due to the presence of essential factors. Healing depended more upon the etiology than the duration of PED. Due to scarcity of literature on serum therapy, further studies are required to establish the efficacy